Drought did not change the linear relationship between chlorophyll fluorescence and terrestrial gross primary production under universal biomes - Jia, Liping; He, Yi; Liu, Wanqing; Li, Yanlin; Zhang, Yaru (Frontiers in Forests and Global Change, 2023)
Satellite observations of sun-induced chlorophyll fluorescence (SIF) are increasingly considered a ‘probe’ for photosynthesis. In recent years the emergence of SIF has facilitated regional and global monitoring of vegetation photosynthesis. On the one hand, there is still controversy about the liner or non-linear SIF-GPP relationship and whether high-temperature events will change the linear relationship. On the other hand, it is unclear whether different vegetation types will affect the SIF-GPP. We used GOSIF and MOD17A2 GPP to study the different relationships under five vegetation types during the long-term climate change period and the extreme drought in 2009/2010 in southwest China. We found that during the long-term climate change period, there was a generally linear SIF-GPP relationship under five vegetation types. The correlation is almost universally maintained at the r2 = 0.92 level. During the drought, the extremely high temperature did not change the linear relationship. Besides the farmland ecosystem, the correlation remained at the r2 = 0.85. In the case of extreme drought, irrigation measures adopted by farmers in response to heat conditions may affect the SIF-GPP relationship of farmland. Our study shows that the linear relationship of SIF-GPP is not influenced by drought on a large scale, and there is a general SIF-GPP relationship in different vegetation types. Our study will provide some help for GPP prediction in diverse ecosystems.